Navigating the double bind – gendered attitudes towards appearance-based exercise in Finland - Grahn, Anna (SAGE Publications, 2025)
Prior studies on physical appearance-related norms, particularly for women, have demonstrated that expectations and standards of the ideal body type – thin and slender – have converged with a normatively healthy and athletic body ideal. Various scholars have concluded that women face inconsistent expectations where they are often supposed to perform physical work and remain cautious about not being labelled as vain. Although considerable progress has been made in this field of research, studies regarding the normative acceptability of appearance-based exercises are limited. This study highlights the norms and attitudes towards appearance-based exercise and the extent to which these attitudes are gendered. It uses an experimental split-ballot design with a population-based survey conducted in Finland in 2016 (N = 1600). The findings suggest that women are more critical than men when evaluating women practising appearance-based exercise. This study uncovers the group-level double standards of appearance-related norms between men and women, that is women are more critical of appearance-based exercise than men. Women face the ‘double bind’ of trying to submit to either feminine or fitness norms and condemning other women for performing the same actions. The study opens new perspectives to the literature on physical appearance as a precarious resource for women.